MGBM (MINYAK GORENG BUAH MERAH) YANG BERMANFAAT DAN BERKHASIAT DI KALANGAN MASYARAKAT - Zipora Kogoya; Eva Susanty Simaremare; Milka Ika Tabuni; Iriani Yarangga; Ordeta Alua (JURNAL PENGABDIAN PAPUA, 2019)
Buah merah plant (Pandanus conoideus Lam) is an original plant from Papua that take an important role in the fulfillment of food needs of the local people in Jayawijaya mountains-Wamena. This plant is also used as a cooking oil spice and useful as traditional medicine, degenerative drugs, HIV and other drugs and can increase endurance. Red fruit crops have appeared to be high value merchandise and export commodities. Red fruit oil is considered a functional oil because it can be used as a preventive agent for various diseases, such as anticancer, antioxidant, antidiabetic, HIV treatment, etc. Red fruit extract products are widely produced in Papua. The selling price in the market ranges from Rp 150.000 to Rp 200.000 per liter. This extract is often forged by adding other oils; such as corn oil, soybean oil, palm oil, sesame oil, and other vegetable oils to gain higher profits. This activity aims to make the red fruit cooking oil products (MGBM) is economical and generate good profits. Methods of implementation are sampling, MGBM product creation, marketing, evaluation, and reporting. The results obtained are the presence of red fruit products with profits from the sale of 20 bottles get a profit of Rp. 1.400.000. Keywords: Buah merah (Pandanus conoideus), Edible Oil, Jayawijaya